Wheat Cultivars With Contrasting Root System Size Responded Differently to Terminal Drought - Figueroa-Bustos, Victoria; Palta, Jairo A.; Chen, Yinglong; Stefanova, Katia; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2020)
In the Mediterranean-type climate of Australia and other parts of the world, end-of- season or terminal drought is the most significant abiotic stress affecting wheat grain yields. The relationship between root system size and tolerance to terminal drought was examined in two wheat cultivars—Bahatans-87 and Tincurrin with large and small root system sizes, respectively. The cultivars were grown in 1.0 m deep PVC columns filled with soil in a glasshouse under well-watered conditions until the onset of ear emergence (Z51) when well-watered and terminal drought treatments were imposed. In the well-watered treatment, >80% soil water capacity was maintained in columns by regular watering, while watering was withheld in the terminal drought treatment. Shoot and root traits, water use, grain yield and yield components were measured. Before imposing the watering treatments, Bahatans-87 had 28% and 63% leaf area and shoot biomass, respectively, higher than Tincurrin. Terminal drought reduced stomatal conductance, leaf photosynthesis and transpiration rates faster in Bahatans-87 than Tincurrin. Terminal drought reduced grain yield in both cultivars, more so in Bahatans-87 (80%) with the large root system than Tincurrin (67%) with the small root system, which was mainly due to a reduction in grain number and grain size in Bahatans-87 and grain size in Tincurrin. In the terminal drought treatment, Bahatans-87 had 59% lower water use efficiency than Tincurrin, as Bahatans-87 used 39% more water and reduced grain yield more than Tincurrin. The lesser reduction in grain yield was associated with slower water extraction by the small root system and slower decline in stomatal conductance, leaf photosynthesis and transpiration rates, but more importantly to faster phenological development, which enabled grain filling to be completed before the severe effects of water stress. Selection for yield in wheat under terminal drought should consider the size of the root system in wheat.